Subak Bentuk Kearifan Lokal Bali Berbasis Tri Hita Karana dan Tantangannya pada Era Globalisasi - Nyoman Suryawan; I Wayan Wiryawan; I Wayan Gata; I Wayan Kandia (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Besides being known for its tourist destinations, Bali also has traditional institutions full of local wisdom known as subak. In the era of globalization triggered by advances in science and technology as well as rapid progress in the field of tourism, this has created problems for the existence of subak itself, both in terms of socio-religious aspects as well as its physical condition. The aim of this research is not only to understand the wisdom of subak but also to know the challenges experienced by subak in the era of globalization. The method used in this research is an exploratory method to reveal phenomena that are fundamentally related to the focus of the problem or object of study. In addition, this research was conducted through a critical ethnographic approach based on a qualitative research paradigm. Subak is a traditional institution that is socio-religious and plays a very important role in distributing water to rice fields in Bali. In carrying out its activities, subak is based on the harmonization philosophy of Tri Hita Karana or the three causes that can give happiness to humans, consisting of parhyangan or human relations with the Creator, pawongan or human relationships with each other and palemahan or relationships between humans and their natural environment. In this era of globalization, which has entered through the rapid development of tourism, it has resulted in many subaks whose functions have begun to be eroded, starting from the decreasing number of subaks caused by the transfer of functions from existing subak lands, to the decreasing desire of the younger generation who pursue the profession of farmers as their livelihood. In addition, the entry of modern culture with the use of chemicals in pest control, has made several species of rice fields disappear. Rituals in subak culture have also begun to be simplified even though in practice it does not reduce the meaning of the ritual itself. Government intervention is needed to save the existence of subak in Bali through improving irrigation, increasing dams that can accommodate water for agricultural irrigation, exemption from rice fields tax, fertilizer assistance or other assistance needed by farmers.